WOMEN AND SAMBEN SPACE: TOURISM GLOBALIZATION AND TRADITION IN KASONGAN - Mila, KARMILAH; Wiendu, NURYANTI; Nindyo, SUWARNO; Bakti, SETIAWAN (DIMENSI (Journal of Architecture and Built Environment), 2014)
The involvement of women in economic activities is a phenomenon that has lasted a long time. An overview of the extensive-role of women confirms that women's involvement context becomes very important to note. One of phenomenon is the “samben” space. The emergence of samben space is a form of adaptation of Kasongan women addressing the growing tourism globalization. In Javanese tradition, women are always become a wife and mother to guard their house. On the other hand, they are also willing to help the family economy by working at home. For this situation they call samben. So the phenomenon of women working from home with an exploration of the whole part of the house is a way for women to adapt to the present but at the same time maintaining cultural traditions to remain a mother and wife.